Sustainable Integrated Clean Environment for Human & Nature - Hashemi, Shervin; Hashemi, Shervin (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, the articles published in the special issue of the journal Sustainability (ISSN 2071-1050), entitled (3z(BSustainable Integrated Clean Environment for Human & Nature(3y (Bare re-printed. The objective of this book is to answer the following questions regarding technical, economic, and social approaches:1. What is the current state of the environment? Is it clean?2. How can we make our environment clean and suitable for humans as well as nature?3. How can we keep our environment clean through sustainable practices? The re-printed research articles and review papers aim to cover the subjects mentioned below: 1. COVID-19 and the sustainability of a clean environment for humans and nature: visions, challenges, and solutions2. Clean technologies and nature-based approaches, including environmental remediation and resource circulation3. Global sanitation, hygiene, and public health issues4. Economic approaches, including the development of economic models, life cycle assessment, and the circular economy5. Social awareness and effective education on human rights for procuring clean air and water Through including the latest studies in the above-mentioned fields, this book addresses the technicians, economists, social activists, and decision-makers who are concerned about clean environment concepts for sustainable development of the current and next-generation through respectful interactions between humans and nature.s
English
Keywords: Technology: general issues; resource-oriented sanitation; sanitation sustainability index; SDG6; sustainability assessment; sustainable development goals; sustainable sanitation; urban geomorphology; sustainable environment; suitability model-GIS; environmental analytical hierarchical process (EAHP); Failaka Island; disinfection; COVID-19; sterility assurance level; medical masks; inactivation; UV irradiation; climate indicators; air quality; environment; pandemic; coronavirus; sustainability; industry 4.0; sustainable investment; corporate social responsibility; sustainable standards; sustainable reporting; smart manufacturing; renewable energy; cleaner production; cattle farming; COVID-19 pandemic; economic point of view; food safety; HOMER; hybrid system; smallholder; thin-film coating; Basic Brown 16; adsorption; durian shell; mechanism; techno-economic analysis; secondhand smoke; time activity; smoke-free; exposure assessment; lockdown; social distancing; mobility; SEM; sustainable development strategies; community development plans; small island developing states; governance; sanitation; water supply; hygiene